A bi-level model for strategic bidding of a price-maker retailer with flexible demands in day-ahead electricity market. (October 2020) - Sharifi, Reza; Anvari-Moghaddam, Amjad; Fathi, S. Hamid; Vahidinasab, Vahid
Highlights: A single-leader multi-follower Stackelberg model is presented for strategic bidding. A decision-making tool is designed for price-maker retailer in electricity market. A DR model is proposed to accommodate adjustability and flexibilities features. A stochastic bi-level model is presented for day-ahead market practices. Abstract: In this paper, a bi-level Stackelberg-based model between an electricity retailer and consumers is presented, in which the upper-level consists of a price-maker retailer (PMR) modeled as the leader who seeks to maximize its own profit by adopting optimal pricing strategies for a pool-based electricity market. At the same time, PMR reduces its risks by encouraging consumers to actively participate in demand response (DR) programs. The lower-level of the model consists of 4 followers, three of them represent customer groups with distinct reactions to DR programs, and their objective function is defined as minimizing the cost of purchased electricity while preserving the welfare level. The fourth follower is the electricity pool, which is responsible for implementation of market mechanism and determination of market clearing price (MCP) with the aim of increasing the consumers' welfare. In the proposed framework, the reaction of consumers to prices and DR programs are also organized and studied in form of several scenarios. The outputs of the proposed model will be enhancing the retailer's profit and determination of the effect of DR programs on power consumption during peak hours as well as consumers' welfare.